Incisional Hernia in a Dog - Lima, Antônio Jackson Sousa; Lima, Wagner Costa; Lima, Dayanne Anunciação Silva Dantas; Sala, Pollyana Linhares; Borges, Talita Bianchin; Quessada, Ana Maria (Acta Scientiae Veterinariae, 2021)
Background: The rupture of the suture in the abdominal wall, but with integrity of the cutaneous suture, results in a condition known as incisional hernia. It is characterized by the protrusion of the abdominal viscera through orifices or areas of the abdominal wall. In most of the cases these defects in the abdominal wall are iatrogenic. The incisional hernia occurs in an intact wall that is weakened by surgical incisions. The available literature on the incidence of incisional hernias in animals is scarce. With the aim to contribute to the information about incisional hernia in animals, it was decided to describe the case of incisional hernia in a female dog after performing ovariohysterectomy (OH). Case: An adult mongrel shelter bitch, of unknown age, weighing 9.5 kg was admitted for OH in a practical class of the veterinary surgical technical discipline. Once the anesthetic condition was established, a retro-umbilical cutaneous incision was made. After opening the abdominal cavity, the bitch was castrated routinely. The abdominal wall was sutured including peritoneum, muscle fascia, and rectus abdominis muscle with nylon thread and U-stitches. The subcutaneous tissue was then sutured with the same thread using Cushing suture. Ten days after the surgery, when the stitches were removed, the bitch revealed an increase in volume at the region of the surgical scar. Incisional hernia was diagnosed after careful palpation. For correction of the hernia, the bitch was submitted to surgical procedure. After the skin opening, an intense inflammatory reaction was observed in the subcutaneous tissue. The inflamed skin and subcutaneous tissue were removed. The abdominal cavity was closed with nylon thread by means of U-stitches. The subcutaneous and skin sutures were the same as the first surgery. Ten days after the second surgery, stitches were removed, and the bitch had fully recovered. Discussion: One of the factors that may have contributed to the occurrence of the hernia was carrying out the surgical procedure in a practical class. The difficulties shown by students are related to the long learning curve, the complexity of the invasive technique, and the lack of ability. The apprentice surgeon can cause injuries in the tissues due to excessive manipulation. Post-incision hernias are acquired and formed when a cavity wall closed by surgery is ruptured. Another factor that may have contributed to the occurrence of the hernia described here is unsatisfactory postoperative care, which may be considered as one of the factors for acute cases of incisional hernias. Information on postoperative care after the patient was returned to the shelter is not available. Therefore, it cannot be ruled out that the patient, in contact with other animals by means of games or even fights, could have ruptured the points, thus causing dehiscence of the suture in the abdominal wall. However, it was concluded that the most probable factors involved in the etiology of the hernia in question were nutritional deficiencies along with the inexperience of the surgeon. The treatment adopted in the patient (herniorrhaphy) was adequate for the correction of the hernia. The technique and the material to be used in the procedure are of great importance, since it must be resistant enough to avoid recurrences. In the patient in question, nylon thread was used in separate U-shaped stitches. In the literature, there are reports that unabsorbable yarns used at separate points present the lowest rate of dehiscence and relapse in the abdominal wall sutures. The incisional hernia can be prevented by preparing the patient for surgery, improving the nutritional requirements, and by a more intense training of the students performing the surgical procedure in the neutering program of dogs and cats during practical classes.